Proteome of the Triatomine Digestive Tract: From Catalytic to Immune Pathways; Focusing on Annexin Expression - Gumiel, Marcia; Mattos, Debora Passos de; Vieira, Cecília Stahl; Moraes, Caroline Silva; Moreira, Carlos José de Carvalho; Gonzalez, Marcelo Salabert; Teixeira-Ferreira, André; Waghabi, Mariana; Azambuja, Patricia; Carels, Nicolas (Frontiers in Molecular Biosciences, 2020)
Rhodnius prolixus, Panstrongylus megistus, Triatoma infestans and Dipetalogaster maxima are all triatomines and potential vectors of the protozoan Trypanosoma cruzi responsible for human Chagas' disease. Considering that the T. cruzi’s cycle occurs inside the triatomine digestive tract (TDT), the analysis of the TDT protein profile is an essential step to understand TDT physiology during T. cruzi infection. To characterize the protein profile of TDT of D. maxima, P. megistus, R. prolixus and T. infestans, a shotgun liquid chromatography-tandem mass spectrometry (LC-MS/MS) approach was applied in this report. Most proteins were found to be closely related to metabolic pathways such as gluconeogenesis/glycolysis, Krebs cycle, fatty acid metabolism, oxidative phosphorylation, but also to the immune system. The enzymes were annotated according to Gene Ontology and KEGG in terms of class, acceptor, and function, while the proteins from the immune system were annotated by reference to the pathways of humoral response, IMD, Toll, Jak-STAT, and MAPK, as available from the Insect Innate Immunity Database (IIID). These pathways were further subclassified in recognition, signaling, response, coagulation and none. Finally, phylogenetic affinities and gene expression of annexins were investigated for understanding their role in the protection and homeostasis of intestinal epithelial cells against the inflammation.